VARIABEL-VARIABEL YANG MEMPENGARUHI PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Chelsy Chelsy; Lina Lina (Universitas Kristen Maranatha, 2013)
The purpose of this study is to analyze and get empirical evidence aboutvariables affecting income smoothing practices of listed manufacturing companiesin Indonesian Stock Exchange. The variables being examined were firm size, risk,profitability, operating leverage, net profit margin and public ownership structure.The study was using 28 manufacturing companies listed in Indonesian StockExchange, with a period between 2008-2010. This research used purposivesampling method in gathering samples. Logistic regression is used as the statisticaltest method. Index Eckel is used to determine the income smoothing practice. Theresult of this research firm size, operating leverage, and public ownership structurehave influence to income smoothing whereas risk, profitability, and net profitmargin did not affect income smoothing.